2021
DOI: 10.1371/journal.pone.0259708
|View full text |Cite
|
Sign up to set email alerts
|

Recent infections among individuals with a new HIV diagnosis in Rwanda, 2018–2020

Abstract: Background Despite Rwanda’s progress toward HIV epidemic control, 16.2% of HIV-positive individuals are unaware of their HIV positive status. Tailoring the public health strategy could help reach these individuals with new HIV infection and achieve epidemic control. Recency testing is primarily for surveillance, monitoring, and evaluation but it’s not for diagnostic purposes. However, it’s important to know what proportion of the newly diagnosed are recent infections so that HIV prevention can be tailored to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
2
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 13 publications
4
13
2
6
Order By: Relevance
“…Enhanced Response efforts to recent infections and/or cases with risk factors/group can be maximized through a strong coordination platform like a Public Health Emergency Operation Center. Nonetheless, the 14.2% finding in the present study is lower than the 30.4% finding in Germany ( 15 ), the 19% report from Singapore ( 16 ) and the 17% report in Uganda ( 17 ), but it is higher than the 9.5% finding from northern China ( 18 ), the 8.6% finding in Kenya ( 19 ), the 6.1% finding from Rwanda ( 20 ) and the 3% finding in Malawi ( 21 ). This difference comes from real variation in HIV incidence in the respective countries or difference in recent infection testing algorisms.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Enhanced Response efforts to recent infections and/or cases with risk factors/group can be maximized through a strong coordination platform like a Public Health Emergency Operation Center. Nonetheless, the 14.2% finding in the present study is lower than the 30.4% finding in Germany ( 15 ), the 19% report from Singapore ( 16 ) and the 17% report in Uganda ( 17 ), but it is higher than the 9.5% finding from northern China ( 18 ), the 8.6% finding in Kenya ( 19 ), the 6.1% finding from Rwanda ( 20 ) and the 3% finding in Malawi ( 21 ). This difference comes from real variation in HIV incidence in the respective countries or difference in recent infection testing algorisms.…”
Section: Discussioncontrasting
confidence: 86%
“…The first variable is being a female, which increases the likelihood of recent infection with over two folds as compared to males, which is also reported by WHO regional office for Africa ( 2 ), and other similar studies from Uganda and China ( 17 , 18 ). The reason might be more females are currently being engaged in risky sexual behaviors to cop-up with the growing living costs in the country, increased anatomical risks or might be associated with minimal women's decision role to have a safe sex ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most people living with HIV (PLHIV) are from developing countries, with sub-Saharan Africa contributing the most significant burden. Despite advances in the knowledge of HIV prevention and treatment, significant numbers of incident HIV infections and AIDS-related deaths continue to happen globally [4] , with an estimated 680,000 AIDS-related deaths in 2020 alone [5] . AIDS is defined as the laboratory diagnosis of HIV infection plus either an opportunistic infection or a CD4 count of below 200/μL [1] .…”
Section: Introductionmentioning
confidence: 99%
“…Rwanda's adult (15 to 64 years) HIV prevalence is 3% with women facing a higher burden compared to men [5,10]. Although efforts such as screening blood donations, increased support for diagnostic services, health education, prevention services such as free condoms and scaling-up of antiretroviral therapy (ART) have greatly reduced HIV incidence in Rwanda, there exist strong gender disparities in terms of HIV prevalence and incidence [11][12][13]. The Rwanda Demographic and Health Survey (RDHS) 2020 further reports that 9% of Rwandan women engage in sexual intercourse with someone else other than their partner.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, regional studies have also shown healthcare providers' HIV knowledge scores to be low, with Rwanda scoring lower than the other countries [23]. Nonetheless, there is a dearth of information regarding comprehensive knowledge about HIV/AIDS among adolescents with most studies focusing on prevalence, incidence and ART uptake/adherence [3,8,10,11,13]. It is therefore crucial to understand and address HIV knowledge gaps among adolescents in order for programs and policymakers to design better and evidence-based behavior change interventions.…”
Section: Introductionmentioning
confidence: 99%